Parents' Gender Role Attitudes and Child Adjustment: The Mediating Role of Parental Involvement. - Wang, Iris Yili; Cheung, Rebecca Y. M. (Sex Roles, 2023)
Parents' gender role attitudes are pertinent to child adjustment. Importantly, parental involvement may help to explain the link between parents' gender role attitudes and child adjustment. In this study, we investigated the differential contributions of mothers' and fathers' gender role attitudes on child adjustment, with the quality of mother and father involvement as mediators. Given that parental involvement is gender-differentiated in the Chinese context, actor and partner effects of mothers' and fathers' gender role attitudes on parental involvement were also examined. Participants were 211 maritally intact families from China, including mothers and fathers of children aged 4 to 7 years old. The findings based on structural equation modeling identified the actor and partner effects of fathers' greater traditional gender role attitudes on a lower quality of mother and father involvement, whereas mothers' greater traditional gender role attitudes were only related to a lower quality of mother involvement. Greater mother and father involvement was further associated with children's greater prosocial behavior. The findings suggested the mediating role of the combined mother and father involvement between fathers' gender role attitudes and children's prosocial behavior. This study underscores the interdependent nature of mothers' and fathers' behavior on child adjustment. The findings inform researchers and practitioners of the importance of reducing both parents' traditional gender role attitudes and enhancing the quality of parental involvement to foster child adjustment.